The Roles of Parents in Preventing Bullying Behavior in Children at Aged 5-6 Years Old - Fono, Yasinta Maria; Dhiu, Konstantinus Dua; Dominic, Midhun; Meo, Vinsensia; Ndange, Sisilia (IJECA (International Journal of Education and Curriculum Application), 2022)
Early childhood is often referred to as the golden age. This age is a very important period for a child. Education in this age range will determine the next stage of child development. This research aims to determine the roles of parents in preventing bullying behavior in children aged 5-6 years old at Early Childhood. This research is a qualitative research. Data collection techniques were using by observation and interview techniques. The data analysis technique were using by reduction, data presentation and conclusion drawing. The results showed that parents play an important role in preventing bullying behavior. Parents apply appropriate parenting styles for children because parenting applied by parents will have an influence on children's behavior. Parenting patterns applied by parents include applying discipline, advising, reprimanding, scolding, directing activities, monitoring activities, and setting an example for children. Parents must build good communication with children and schools related to child development so that there is a continuity of children's attitudes at home and at school.